PENGARUH PENILAIAN KINERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI RUMAH SAKIT CIPTO MANGUNKUSUMO - Lalan Pradika; Irwan Indriyanto (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
Purpose to determine the effect of performance appraisal and motivation the work productivity of employees at the HR Department of Dr. National General Hospital. Cipto Mangunkusumo. Using a saturated sample/census by taking the entire population, so that the sample taken is all employees in the HR department of Dr. RSUP. Cipto Mangunkusumo. In collecting data the researchers used a questionnaire method. 1) The results of hypothesis testing indicate that there is no effect of performance appraisal on work productivity. 2) The results of hypothesis testing indicate that there is an effect of work motivation on work productivity. 3) The results of hypothesis testing indicate that there is an effect of performance appraisal and work motivation simultaneously on work productivity.